Antimicrobial agents annual. - Society for Industrial Microbiology (U.S.); Conference on Antimicrobial Agents (1960 : Washington, D.C.). ([Washington, D.C. : Society for Industrial Microbiology] ; New York : Distributed by Plenum Press, 1961)
Proceedings of the Conference on Antimicrobial Agents, 1st, 1960.
Issued by: Society for Industrial Microbiology.
SERBIB/SERLOC merged record
Keywords: Antibiotics -- Congresses; Chemotherapy -- Congresses; Anti-Bacterial Agents -- Congresses; Antibiotiques -- Périodiques.